Quenched Electrochemiluminescence Imaging using Electro-Generated Substrate for Sensitive Detection of Catalase as Potential Enzyme Reporter System. (20th June 2017) - Inoue, Yuki; Saito, Masato; Yoshikawa, Hiroyuki; Tamiya, Eiichi
Abstract: In this paper, the quenching of electrochemiluminescence (ECL) imaging by enzyme reaction localized in the multi-chamber electrode using electro-generated substrate is described as a potential candidate for reporter system. Presence of catalase in micro sized reaction chamber convert H2 O2 as substrate to O2 and H2 O, which consumed the coreactants for ECL resulting in quenching of the ECL. In the presented system, H2 O2 which is the substrate for enzyme was introduced when negative potential was applied to the electrode thus the timing of enzyme reaction was electrochemically regulated. Highly sensitive signal-off ECL detection was shown by combining electrode generated substrate ECL technique with the use of magnetic nanoparticles coated with catalase for a construction of sensitive reagent-less sensing system. The substrate was successfully generated at applied potential between −1 to −0.4 V in multichamber electrode and the substrate confinement within the chamber was observed up to 60 seconds generation time. The constructed system demonstrated detection limit of 90 fM catalase measured in 60 seconds in ambient temperature. The observations were interpreted in view of enzyme kinetics and chemical dynamics within the micro reaction chamber. The two fundamentals worked in concert for the quenching of ECL signal near the bottom of the chamber where the electrode surface was located. The variance of ECL signal of localized enzyme reactions in chambers were shown to result from uneven distribution of the magnetic nanoparticles showing possibility of independent detection in individual chambers.